(untitled) - Cole, Don (Guiford, 2002)
This reader is a collection of current articles from sources such as Foreign Policy, The Brookings Review and The World & I. Articles examine specific microeconomic and macroeconomic issues; income distribution and economic justice; and the changing global economy.
Keywords: Economics